1996
DOI: 10.1093/jac/37.2.323
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental endocarditis caused by multidrug resistant Enterococcus faecium with ramoplanin and penicillin

Abstract: Antibiotic resistant strains of enterococci are being isolated with increasing frequency. Effective treatment of infections caused by Enterococcus faecium resistant to ampicillin, vancomycin and aminoglycosides has not been established. We studied the activity of ramoplanin, a new lipoglycopeptide antibiotic, against two strains of multidrug resistant E. faecium. In time kill studies, ramoplanin was bactericidal against both strains, but not in the presence of 50% serum. The combination of ramoplanin and penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In 2006, Oscient Pharmaceuticals evaluated orally dosed ramoplanin, which is not systemically absorbed, in late-stage trials for the treatment of Clostridium difficile -associated diarrhea (CDAD) and VRE gastrointestinal colonization ( 13 16 ). Despite being administered intravenously to mice ( 17 , 18 ), rats ( 17 , 18 ), and rabbits ( 19 ) in in vivo models, parenteral administration of ramoplanin in humans is complicated due to hemolysis ( 13 , 18 , 20 ) and loss of activity due to hydrolysis of the depsipeptide ester ( 14 ). Nano Therapeutics, Inc., acquired the rights to develop ramoplanin in 2009 and recently announced that a phase IIb trial has been scheduled for September 2014 to investigate the use ramoplanin (coded NTI-851) as a targeted prophylaxis for recently treated patients with C. difficile infection (CDI) at high risk for infection relapse ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Oscient Pharmaceuticals evaluated orally dosed ramoplanin, which is not systemically absorbed, in late-stage trials for the treatment of Clostridium difficile -associated diarrhea (CDAD) and VRE gastrointestinal colonization ( 13 16 ). Despite being administered intravenously to mice ( 17 , 18 ), rats ( 17 , 18 ), and rabbits ( 19 ) in in vivo models, parenteral administration of ramoplanin in humans is complicated due to hemolysis ( 13 , 18 , 20 ) and loss of activity due to hydrolysis of the depsipeptide ester ( 14 ). Nano Therapeutics, Inc., acquired the rights to develop ramoplanin in 2009 and recently announced that a phase IIb trial has been scheduled for September 2014 to investigate the use ramoplanin (coded NTI-851) as a targeted prophylaxis for recently treated patients with C. difficile infection (CDI) at high risk for infection relapse ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…No agent has been demonstrated to have efficacy for this purpose, despite the study of several candidates (novobiocin, doxycycline, bacitracin) (14,15,18,28). Ramoplanin, a glycolipodepsipeptide antimicrobial that is not systemically absorbed, has been demonstrated to have activity against VRE and has been studied as a locally active agent for the suppression of colonization (11,13,21).In a multicenter, randomized, double-blind, placebo-controlled phase II trial, ramoplanin was shown to be safe and effective at suppressing VRE to undetectable levels (at day 7) in 80 to 90% of treated patients (29). Patients colonized with VRE but without evidence of active infection were randomized to receive placebo or ramoplanin at 100 or 400 mg orally twice a day for 7 days.…”
mentioning
confidence: 99%
“…No agent has been demonstrated to have efficacy for this purpose, despite the study of several candidates (novobiocin, doxycycline, bacitracin) (14,15,18,28). Ramoplanin, a glycolipodepsipeptide antimicrobial that is not systemically absorbed, has been demonstrated to have activity against VRE and has been studied as a locally active agent for the suppression of colonization (11,13,21).…”
mentioning
confidence: 99%
“…However, we were able to find only two reports of in vivo efficacy: one in the patent literature, in which ED 50 values ranging from 1 to 5 mg/kg for mouse septicemia induced by S. aureus or E. faecium were reported (36), and the other in a peer-reviewed journal, where efficacy in rabbit endocarditis was observed only in combination with penicillin (8). Several publications commented on instability of ramoplanin in animal serum (1, 12) although we could not find any data substantiating such a claim.…”
Section: Discussionmentioning
confidence: 99%
“…Its rapid bactericidal activity (5, 6) made ramoplanin a promising candidate for treating serious, life-threatening infections. Ramoplanin is effective in systemic use in animal models of infection although only a few studies have reported efficacy data (7,8). Such use, however, has been hampered by ramoplanin hemolytic activity when the compound is administered intravenously (i.v.).…”
mentioning
confidence: 99%